Diabetes Fact Sheet in Korea, 2016: An Appraisal of Current Status - Jong Chul Won; Jae Hyuk Lee; Jae Hyeon Kim; Eun Seok Kang; Kyu Chang Won; Dae Jung Kim; Moon-Kyu Lee (Diabetes & Metabolism Journal, 2018)
BackgroundThis report presents the recent prevalence and comorbidities related to diabetes in Korea by analyzing the nationally representative data.MethodsUsing data from the Korea National Health and Nutrition Examination Survey for 2013 to 2014, the percentages and the total number of subjects over the age of 30 years with diabetes and prediabetes were estimated and applied to the National Population Census in 2014. Diagnosis of diabetes was based on fasting plasma glucose (≥126 mg/dL), current taking of antidiabetic medication, history of previous diabetes, or glycosylated hemoglobin (HbA1c) ≥6.5%. Impaired fasting glucose (IFG) was defined by fasting plasma glucose in the range of 100 to 125 mg/dL among those without diabetes.ResultsAbout 4.8 million (13.7%) Korean adults (≥30 years old) had diabetes, and about 8.3 million (24.8%) Korean adults had IFG. However, 29.3% of the subjects with diabetes are not aware of their condition. Of the subjects with diabetes, 48.6% and 54.7% were obese and hypertensive, respectively, and 31.6% had hypercholesterolemia. Although most subjects with diabetes (89.1%) were under medical treatment, and mostly being treated with oral hypoglycemic agents (80.2%), 10.8% have remained untreated. With respect to overall glycemic control, 43.5% reached the target of HbA1c <7%, whereas 23.3% reached the target when the standard was set to HbA1c <6.5%, according to the Korean Diabetes Association guideline.ConclusionDiabetes is a major public health threat in Korea, but a significant proportion of adults were not controlling their illness. We need comprehensive approaches to overcome the upcoming diabetes-related disease burden in Korea.